Authority in the Management and Utilization of Agrarian/Land Resources in Indonesia - Firman Muntaqo; Febrian; Alip Dian Pratama; Fadillah Mursid (Universitas Sriwijaya, 2026)
As a nation founded upon belief in the One Almighty God, Indonesia recognizes that all things in the heavens and on earth, including agrarian resources and land, ultimately belong to God. Accordingly, the Indonesian nation possesses only the authority to manage and utilize agrarian resources as national wealth, resources, and assets for the greatest prosperity of the people. The Indonesian state acts merely as the recipient of a mandate from the nation to exercise such authority and is not the owner of agrarian resources or land. This study examines the relationship between the Indonesian nation, the state, and agrarian/land authority within the framework of Indonesian agrarian law. It argues that authority over land management and utilization should be centralized under the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) to prevent overlapping authority and disputes among government institutions. Other ministries requiring land for the performance of their duties should obtain delegated authority through Management Rights Certificates issued by ATR/BPN. The study further highlights that the prevailing interpretation of state control over land has shifted toward viewing the state as the holder of ulayat rights, despite such a concept not being recognized under the Basic Agrarian Law (UUPA). This interpretation has contributed to legal uncertainty, conflicts of authority, unequal land distribution, and the denial of the eternal magical-religious relationship between indigenous communities and their customary lands, including cases such as Rempang Island. The exclusion of ulayat land from land registration under Government Regulation Number 24 of 1997 further weakens legal certainty for customary communities. This paper concludes that agrarian legal politics in Indonesia should reaffirm that the state merely exercises delegated authority, while the Indonesian nation remains the true holder of authority over agrarian resources and land.